(untitled) (Research, Society and Development, 2021)
The Academic League of Functional and Sports Nutrition (LANFE) was founded by students in order to improve theoretical and practical knowledge on functional and sports nutrition. The aim of this study was to report the experience of creating and implementing an extension program of the 1st academic league (AL) in a nutrition undergraduation course at a public university in the State of Rio de Janeiro, discuss the performed activities and evaluate their impact. This study is qualitative-quantitative and descriptive type, and reports the creation experience and activities of the league´s first year. In the evaluation questionnaires applied to internal and external community, 99.2% of participants (n = 123) believed in the importance of creating an AL for the Nutrition Course. Regarding the activities carried out by LANFE, 100% of the participants (n = 15) of the Workshop on functional gastronomy about cocoa considered the event´s quality level to be “very good”, as well as the support to the questions and concerns exposed. Furthermore, 85.3% of LANFE´s I Symposium participants (n = 34) demonstrated a degree of satisfaction "very good". In this way, the academic league proved to be an important teaching and learning tool, mobilizing students and professionals in favor of the construction and sharing of scientific knowledge, thus contributing to the training of undergraduate students in nutrition.